The Treatment Paradigm for the Implantable Miniature Telescope. Issue 1 (June 2016) - Hau, Vincent; London, Nikolas; Dalton, Michelle
Abstract Advanced or end-stage age-related macular degeneration (AMD) results in significant visual impairment and a substantially reduced quality of life for patients. Therapeutic options for people with bilateral moderate or profound vision loss caused by end-stage AMD are limited. Although medical treatment capable of reversing the functional vision loss that results from end-stage AMD is non-existent, there are now treatments that can reverse some of that functional vision loss, including the implantable miniature telescope (IMT). This review article discusses the science behind the IMT, evaluates the data from clinical studies, and weighs the pros and cons of the technology.